Relações dialógicas no gênero postagem de facebook sobre o processo eleitoral de 2014 - Pinto Filha, Maria das Dores de Lima (2017)
This dissertation proposes to delimit as an object of study the dialogical relations present in the facebook post genre on the Brazilian electoral process of 2014, specifically in how the discourses materialized in the genre and circulate mediatically. We chose the electoral period of 2014 in view of the expansive number of posts about the discursive polemics in the candidates' proposals, which constitutes an electoral scenario of laughter and irony. We made a cut of this material with the objective of analyzing the dialogical relations that were constructed in concrete statements in messages of political nature circulated in the facebook social network. We use as theoretical reference the works developed by Bakhtin and the Circle, besides them, we use the theoretical considerations of researchers of the area of studies of the basic bakhtinian discourse, such as: Barros (2003); Faraco (2003); Souza (2002) and Fiorin (2006). This categorization responded to our research questioning: what dialogical relations form the posts about the 2014 electoral process in Brazil? Our hypotheses point to relationships of irony, derision, and fallacies. It is possible to affirm that these relations both influence the vote and predict results of the polls. Methodologically, we classify our study as an explanatory and qualitative approach, since, our path was to identify factors that determine or contribute to the occurrence of the phenomena (GIL, 2007). Our results confirmed our hypotheses that verbal and extra-verbal materiality have dialogic relations of irony, scorn, and fallacies.